Reasoning Rebellion: E.P. Thompson, British Marxist Historians, and the Making of Dissident Political Mobilization - Palmer, Brian (Labour/Le Travailleur, 2002)
Abstract This paper commences with a suggestion that “the British Marxists” may well be a more diverse group than has generally been recognized. It concerns itself with the formation of the first British New Left in the1950s. The content of the E.P. Thompson and John Saville edited journal, The New Reasoner is examined, with attention paid to the publication’s internationalism, its use of critical social science, the accent placed on culture, and the stress on organization. To the extent that The New Reasoner failed in its in tended aim of building and sustaining a New Left, the paper closes with some suggestions about the implications of this failure, especially as it related to E.P. Thompson’s historiographical contributions, in which the influence of The Making of the English Working Class (London 1963) loomed large.